Clinicopathological study of surgery for pulmonary metastases of hepatoblastoma with indocyanine green fluorescent imaging. Issue 7 (10th December 2021) - Yoshida, Misa; Tanaka, Mio; Kitagawa, Norihiko; Nozawa, Kumiko; Shinkai, Masato; Goto, Hiroaki; Tanaka, Yukichi
Abstract: Background: The prognosis of metastatic hepatoblastoma remains poor; to improve it, pulmonary metastasis must be controlled. Indocyanine green (ICG) fluorescent imaging has been used recently for lung metastasectomy. The objective of our study was to clarify the usefulness of ICG imaging for lung metastasectomy of hepatoblastoma using detailed clinicopathological analysis. Procedure: Patients with hepatoblastoma who underwent resection of pulmonary metastases with ICG fluorescent imaging were studied using a retrospective analysis of clinical information, a review of their surgical records, and a histological analysis of their metastatic nodules. Results: Sixteen patients were enrolled. In total, 61 ICG imaging‐guided pulmonary metastasectomies were performed, and 350 ICG‐positive and 23 ICG‐negative specimens were identified. Tumors were confirmed in 250 of the ICG‐positive specimens, including eight nonpalpable nodules, on microscopic examination. ICG‐positive and tumor‐negative specimens showed histological changes suggesting the regression of a tumor or bloodstream disturbance. Conclusions: Surgical resection is one of the few treatment strategies available to patients with hepatoblastoma with multiple relapses of pulmonary metastasis resistant to chemotherapy. This study demonstrates the high sensitivity of ICG imaging and that thorough metastasectomy can be achieved with ICG imaging. Because a number of false‐positive specimens were detected, further optimization of the dose of ICG and the timing of its administration, and establishment of detection of ICG‐positive, tumor‐negative nodules during surgery are important issues. Several false‐negative specimens were also detected, suggesting the presence of ICG‐negative metastatic tumors. Palpation during surgery and imaging studies remain essential for detecting metastatic lesions, even in the era of ICG imaging.